(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article reflects on the establishment of relations between Uzbekistan and Germany during the years of independence, and qualitative changes in the cooperation between them in the socio-economic and cultural spheres.